2016
DOI: 10.1101/gad.284323.116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for oncohistone H3 recognition by SETD2 methyltransferase

Abstract: High-frequency point mutations of genes encoding histones have been identified recently as novel drivers in a number of tumors. Specifically, the H3K36M/I mutations were shown to be oncogenic in chondroblastomas and undifferentiated sarcomas by inhibiting H3K36 methyltransferases, including SETD2. Here we report the crystal structures of the SETD2 catalytic domain bound to H3K36M or H3K36I peptides with SAH (S-adenosylhomocysteine). In the complex structure, the catalytic domain adopts an open conformation, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
140
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(151 citation statements)
references
References 30 publications
10
140
1
Order By: Relevance
“…Mutations at H3.3K36 result in genome-wide loss of H3K36 tri-methylation and can directly stimulate tumor formation [167, 168]. Similar to the mechanism by which K→M mutations at H3K9 and H3K27 “trap” or “poison” their respective methyltransferase enzymes [169172], the H3.3K36M mutation rearranges the active center of SETD2 to provide a high affinity binding site for the H3.3K36M histone tail, thus explaining how a single histone mutation can impart a tumor phenotype [173]. As H3K36me is lost from the genome, a redistribution of H3K27me3 by PRC2 occurs across the genome [168].…”
Section: The Role Of Setd2 and H3k36 Methylation In Cancermentioning
confidence: 99%
“…Mutations at H3.3K36 result in genome-wide loss of H3K36 tri-methylation and can directly stimulate tumor formation [167, 168]. Similar to the mechanism by which K→M mutations at H3K9 and H3K27 “trap” or “poison” their respective methyltransferase enzymes [169172], the H3.3K36M mutation rearranges the active center of SETD2 to provide a high affinity binding site for the H3.3K36M histone tail, thus explaining how a single histone mutation can impart a tumor phenotype [173]. As H3K36me is lost from the genome, a redistribution of H3K27me3 by PRC2 occurs across the genome [168].…”
Section: The Role Of Setd2 and H3k36 Methylation In Cancermentioning
confidence: 99%
“…Similar phenotypes were also observed in chondroblastoma cells that contain K36M mutations. Similar to K27M that sequesters EZH2, the K36M mutant inhibits H3K36 methyltransferases, including NSD1, NSD2 and SETD2 in vitro [118], and reduces global H3K36 methylation in vivo [119, 120]. Loss of H3K36 methylation leads to increased H3K27me3 in the intergenic regions, redistribution of the PRC1 complex from its target genes, and consequently, upregulation of PRC1-repressed target genes known to block mesenchymal differentiation [119].…”
Section: Introductionmentioning
confidence: 99%
“…Structural studies of the SETD2 SET domain have revealed a basic patch along the path of the H3 amino-terminal tail as it extends from the catalytic site 23,24 . We speculated that such a feature could provide the basis of a specific enhanced interaction between SETD2 and H3.3S31ph nucleosome substrates and that these interactions might link the augmented enzymatic activity we observed to structural properties.…”
mentioning
confidence: 99%